2018
DOI: 10.1016/j.joep.2018.01.006
|View full text |Cite
|
Sign up to set email alerts
|

“Facta non verba”: An experiment on pledging and giving

Abstract: This paper builds an experiment to investigate whether asking people to state how much they will donate to a charity (to pledge) can increase their actual donation. Individuals' endowment is either certain or a random variable. We study different types of pledges, namely private, public and irrevocable ones, which differ in individual cost of not keeping a promise. Public pledges appear to be associated to lower donation levels. Irrevocable pledges ensure an amount of donations equal to donations in absence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…More than 80% of respondents both agreed they reflected on equity and fulfilled their pledge, indicating excellent engagement with those who pledged. In planning for the original campaign, the IWill team attempted to increase pledge fulfillment through several methods: public recognition of pledges and pledgemakers, 15 , 16 providing information to assist pledge completion, and offering a variety of pledges to choose from. In this follow-up survey, we found that people who made public pledges did report fulfilling their pledge at significantly higher rates, but whether public pledges were a driver for completion, or there was an association between allowing your pledge to be public and thinking that you fulfilled it, remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More than 80% of respondents both agreed they reflected on equity and fulfilled their pledge, indicating excellent engagement with those who pledged. In planning for the original campaign, the IWill team attempted to increase pledge fulfillment through several methods: public recognition of pledges and pledgemakers, 15 , 16 providing information to assist pledge completion, and offering a variety of pledges to choose from. In this follow-up survey, we found that people who made public pledges did report fulfilling their pledge at significantly higher rates, but whether public pledges were a driver for completion, or there was an association between allowing your pledge to be public and thinking that you fulfilled it, remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…This could be related to the increased tendency of men to make public pledges. 15 , 16 Alternatively, like others with privilege, men may be less likely to recognize gender inequities, or to actively reframe inequities they do acknowledge. 22 , 23 Alternatively, men may be more optimistic about prospects for gender equality, 24 or feel more in control of their surroundings, an idea supported by the preponderance of men in this study that felt they had the power to create gender equity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing donations in a sample of US churches, Peifer (2010) finds that donations are not higher in churches that use pledge cards. Others find that hard pledges (e.g., pledges that are signed with the participants' and others' initials, or pledges that are made public, or pledges that are combined with asking subjects to recall past selfless acts) have a positive effect on donations (see Capra et al., 2021; Chou et al., 2020; Cotterill et al., 2013; Sutan et al., 2018). Finally, Andreoni and Serra‐Garcia (2019) show that when participants are given an option to make a pledge to donate on a future date in addition to donating now, overall donations do not increase.…”
Section: Introductionmentioning
confidence: 99%